Paging and Location Management in IEEE 802.16j Multihop Relay Network - Kuan-Po Lin; Hung-Yu Wei (Journal of Computer Systems, Networks, and Communications)
IEEE 802.16j is an emerging wireless broadband networking standard that integrates infrastructure base stations with multihop relay technology. Based on the idle mode operation in IEEE 802.16j, we propose a novel location management and paging scheme. It integrates the paging area-based and the timer-based location update mechanism. In paging area-based scheme, an idle mode mobile station updates when it moves to a new paging area. In timer-based scheme, an idle mode MS updates when the location update timer expires. In this work, we formulate the mathematical model to evaluate the performance of the proposed paging scheme. A new random walk mobility model that is suitable for modeling in multihop relay network is created. Optimization of location update timer is also investigated.